Comprehensive Assessment of Medical Clinic Departments: A Critical Analysis of Interdepartmental Synergy, Challenges, and Innovations - AlDossary , Samar Salem; Ereja, Fadi Faiq; Aljowaie , Rana Mansour; Alqahtani, Abdullah Mubarak; Alsowiyeh, Mohamaad Abdulaziz Mohammed; Aleidan, Eidan Mohammad; Alkhathlan, Turki Abdullah; Alsikhan, Abdullelah Ibrahim; Alqarni, Abdullah Ali; Alharbi, Jahaz Raja (Journal of Ecohumanism, 2024)
Modern medical clinics operate as interconnected ecosystems comprising various departments, each playing a vital role in patient care delivery. This article critically examines the dynamics of interdepartmental synergy within medical clinics, highlighting the benefits of collaboration, such as improved patient outcomes and operational efficiency. It also identifies persistent challenges, including communication barriers, resource constraints, and cultural differences, which hinder effective collaboration. Furthermore, the article explores innovative solutions like Electronic Health Records (EHR), lean management principles, and AI applications that enhance interdepartmental coordination. The findings emphasize the need for comprehensive strategies combining technological advancements and cultural shifts to foster seamless collaboration and improve healthcare delivery.